Comparative analysis of Anti-Money Laundering (AML) and Counter Terrorist Financing (CTF) regimes in the UK and USA - Ngcetane-Vika, Thelela (My University, 2022)
This paper examines the Anti-Money Laundering (AML) initiatives and Counter Terrorist Financing (CTF) approaches in the United Kingdom (UK) and United States of America (USA). Furthermore, it examines the various regulatory frameworks in the above-mentioned jurisdictions. AML/CTF regulations are very critical for the security of economies and societies because they provide frameworks and guidelines for detecting and combating money laundering and other associated crimes. Some of the significant statutory frameworks are: The Bank Secrecy Act (BSA) in the United States, the USA Patriot Act, the Anti-Money Laundering Directives (AMLDs) in Europe, the Sanctions and Anti-Money Laundering Act (SAMLA) in the United Kingdom, and the Proceeds of Crime (Money Laundering) and Terrorist Financing Act (PCMLTFA) in Canada are some examples of these laws. The paper used legal methodologies to explicate the phenomenon under investigation. A doctrinal methodology hinges upon analysis of existing case laws, statutes and other primary sources to understand better the legal proposition. The study established that AML and CTF compliance is one of the important outcomes beneficial to combating Money Laundering and Terrorist Financing. Key Words: Money laundering, Terrorist financing, Regulatory frameworks, Compliance
Keywords: Compliance; Money laundering; Regulatory frameworks; Terrorist financing